TAVI for aortic regurgitation using dedicated devices. A systematic review - Ahmed Hassan; Mahmoud Abdelshafy; Rehab Adel Diab; Hendrik Wienemann; Matti Adam; Santiago García; Marwan Saad; Mohammad Abdelghani (REC: Interventional Cardiology (English Ed.), 2025)
ABSTRACT Introduction and objectives: Transcatheter aortic valve implantation (TAVI) for pure aortic regurgitation is challenging due to inadequate device anchoring and increased risks of device embolization and paravalvular regurgitation (PVR). This study aimed to review the safety and efficacy of TAVI for aortic regurgitation with devices specifically designed for this indication. Methods: A comprehensive search of PubMed, Web of Science, Cochrane Library, and major conference archives up to April 2024 identified 143 unique results based on predefined criteria. Results: Fifteen studies (n = 788 patients) were included, with J-Valve used in 357 patients and JenaValve in 431. Men represented 51% of the cohort, with a mean age of 74.7 ± 8.8 years and an STS-PROM score of 5.8 ± 4.9%. Transapical and transfemoral access routes were used in 62.7% and 37.3% of patients, respectively. Overall, procedural success was achieved in 95.9% of cases; surgical conversion was required in 1.8%, device migration/embolization occurred in 3.2%, and a second valve (in-valve) was required in 2.0% of patients. At 30 days, 95.5% of patients were alive, and device success was reported in 93.3% of cases. Mild PVR was observed in 18.0% of patients, moderate-to-severe PVR in 1.7%, and permanent pacemaker implantation (PPI) was required in 13.0%. In studies focusing on transfemoral procedures (all using JenaValve), the pooled estimates showed a procedural success rate of 97.8% (95%CI, 94.4-100), device success of 97.0% (95%CI, 94.8-99.2), 30-day mortality of 1.96% (95%CI, 0.20-3.72), moderate-to-severe PVR of 0.47% (95%CI, 0.00-1.47), and PPI requirement of 18.7% (95%CI, 13.9-23.4) Conclusions: This systematic review of relatively small observational studies demonstrates the safety and favorable early outcomes of TAVI using J-Valve and JenaValve in patients with pure aortic regurgitation, especially when the transfemoral approach is used. Nevertheless, the need for PPI remains frequent.